The protein-protein interaction-mediated inactivation of PTEN - De Melo, J; He, L; Tang, D (Current molecular medicine, 2014)
PTEN (Phosphatase and Tensin homologue deleted on chromosome 10, 10q23.3) is the dominant phosphatase responsible for the dephosphorylation of the 3-position phosphate from the inositol ring of phosphatidylinositol 3,4,5 triphosphate (PIP3), and thereby directly antagonizes the actions mediated by Phosphatidylinositol-3 Kinase (PI3K). PI3K functions in numerous pathways and cellular processes, including tumourigenesis. Therefore, mechanisms regulating PTEN function, either positively or negatively are of great interest not only to oncogenesis but also to other aspects of human health. Since its discovery in 1997, PTEN has been one of the most-heavily studied tumour suppressors and has been the subject of numerous reviews. Most investigations and reviews center on PTEN's function and its regulation. While the regulation of PTEN function via genetic and/or epigenetic mechanisms has been extensively studied, the impact of protein-protein interaction on PTEN function remains less clear. Recent research has revealed that PTEN can be specifically inhibited by its interaction with other proteins, which are collectively termed PTEN-negative regulators (PTENNRs). This review will summarize our current understanding on the protein network that influences PTEN function with a specific focus on PTEN-NRs.